(untitled) (Contemporary Journal of Social Science Review, 2025)
The research investigated the relationship among work ethic, work engagement and innovative work behavior in banking officers. The hypotheses of the study were that work ethic and work engagement would have a positive relationship with innovative work behavior. Moreover, work ethic and work engagement would be positive predictors of innovative work behavior and work engagement would mediate the relationship between work ethic and innovative work behavior in banking officers. A correlational design was adopted to conduct the research. The research sample consisted of 199 banking officers, both men and women, with an age range between 21 and 59 (M=31.73, SD=7.44), from public and private banks of Lahore. The findings revealed that work ethic had a positive correlation with work engagement and innovative work behavior. Furthermore, work ethic was a positive predictor of work engagement and innovative work behavior. Along with that, work engagement mediated the relationship between work ethic and innovative work behavior. The implications of the study include, introducing policies and designing training programs in the banking sector that promote a culture of strong work ethic and work engagement leading to innovative work behavior in banking officers.